Biodiversity Data Model (BiDaM) Using Object Relational Approach: Conceptual Framework - Wahid, Mohd. Taib; Kamruzzaman, A. Z. M.; Mohamed Shariff, Abdul Rashid; Selamat, Harihodin (2005)
The extensive research has been performed on plant biodiversity and even on mangrove area recent years; managing plant biodiversity data with database system still poses many challenges. Plant biodiversity is the variety of different types of plants species that growth in various landscape. There are phenomenal growths in the area of biodiversity studies, largely motivated by its economic and humanitarian. Various data models, query languages and techniques have been proposed by many researchers. Traditional database systems (built on relational hierarchical and network models) which are widely used for commercial applications such as banking fail to meet the modeling and processing requirements of the biodiversity data. Recently developed BODHI (Biodiversity Object Database arcHItecture) data model which is designed based on Indian plant biodiversity and only support spatial data. Integration between plant Bio-diversity data (BODHI) and geographical data with event-based approach can make an enhancement for the plant biodiversity data analysis and data manipulation. In addition, most of the data models are relational model. However, relational model can not support temporal data (time) effectively; it is best for spatial data (space). The main objective of the present study is to design a conceptual data model which will be later on complete data model for plant biodiversity. Conceptual data model is the extension of BODHI data model by using object relational data modeling and event-based approach to support temporal data. Therefore, conceptual data model by using object relational and event based is an appropriate approach to design a plant biodiversity data model. Moreover, Forest department, land and agricultural management and other related research organization could be benefited from the outcome of this model.